2010
DOI: 10.1371/journal.pone.0010370
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin-Derived Dimers Have Greatly Improved Anti-Cytomegalovirus Activity Compared to Artemisinin Monomers

Abstract: BackgroundArtesunate, an artemisinin-derived monomer, was reported to inhibit Cytomegalovirus (CMV) replication. We aimed to compare the in-vitro anti-CMV activity of several artemisinin-derived monomers and newly synthesized artemisinin dimers.MethodsFour artemisinin monomers and two novel artemisinin-derived dimers were tested for anti-CMV activity in human fibroblasts infected with luciferase-tagged highly–passaged laboratory adapted strain (Towne), and a clinical CMV isolate. Compounds were evaluated for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 40 publications
0
45
0
Order By: Relevance
“…Artemisinin derivatives were originally reported to inhibit CMV replication (7,17), and we have shown that artemisininderived dimers are highly potent inhibitors of CMV replication compared to their monomeric counterparts (2). We now report that AS and 838 have no activities against selected alpha-and gammaherpesviruses.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Artemisinin derivatives were originally reported to inhibit CMV replication (7,17), and we have shown that artemisininderived dimers are highly potent inhibitors of CMV replication compared to their monomeric counterparts (2). We now report that AS and 838 have no activities against selected alpha-and gammaherpesviruses.…”
Section: Discussionmentioning
confidence: 77%
“…We recently reported on the highly potent anti-CMV activities of arteminisin-derived dimers (2). We also identified among a series of dimers the most potent anti-CMV compound, dimer diphenyl phosphate (molecular weight, 838).…”
mentioning
confidence: 99%
“…The compounds used in this study and their mechanisms of action, when known, are listed in Table 1. Artemisinins (monomers and dimers), cardiac glycosides, and U0126 were reported to inhibit CMV replication and were therefore selected for this study (24)(25)(26)(27)(28)(29). The multikinase inhibitor sunitinib has not previously been reported to inhibit CMV replication, but other kinase inhibitors have been shown to inhibit CMV in vitro (30).…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, there is not yet a thorough evaluation of its efficacy but only sporadic reports of its in vivo anti CMV activity with contrasting results [57]. Interesting insights come from artemisinin-derived dimers, novel compounds with more potent in vitro anti-CMV effects [58,59] the efficacy of which remains to be addressed.…”
Section: Artesunate -The Antimalarialmentioning
confidence: 99%